The enigma of 7q36 linked autosomal dominant limb girdle muscular dystrophy. Issue 8 (3rd August 2010) - Sandell, Satu; Huovinen, Sanna; Sarparanta, Jaakko; Luque, Helena; Raheem, Olayinka; Haapasalo, Hannu; Hackman, Peter; Udd, Bjarne
Abstract : Introduction: Two families with autosomal dominant limb girdle muscular dystrophy (LGMD) have previously been linked to a locus on chromosome 7q36 10 years ago. The locus has been termed both LGMD1D and 1E, but because of lack of additional families to narrow down the linked region of interest, this disease has remained elusive. Methods: A large Finnish family was clinically and genetically investigated. Laboratory parameters were determined, including creatine kinase (CK) value, neurographic and electromyography studies, cardiac and respiratory function examinations, muscle biopsies and muscle imaging by CT or MRI. Results: Patients had onset of muscle weakness in the pelvic girdle between the fourth and sixth decades with an autosomal dominant pattern of inheritance. CK values were slightly elevated and electromyography was myopathic only. Muscle biopsies showed myopathic and/or dystrophic features with very minor rimmed vacuolation and protein aggregation findings. Molecular genetic analysis indicates linkage of the disease to the locus on chromosome 7q36 completely overlapping with the previously reported locus LGMD1D/E. Discussion: Advancement towards the causative gene defect in the 7q36 linked disease needs new additional families to narrow the region of interest. The phenotype in the previously linked families has not been reported in full detail, which may be one reason for the shortage of additional families. A comprehensive clinical and morphological phenotype of chromosome 7q36 linked autosomal dominant LGMD with a restricted and updated 6.4 Mb sized haplotype is reported here.